تحليل الصراعات الاجتماعية في رواية دم لفطير صهيون: حارة اليهود لنجيب الكيلاني (منهج سوسيولوجي الأدب بنظرية لويس ألفريد كوزر) - Nur Arifah, Nadia; Gamasari, Rita (Journal of Arabic Language and Literature (ALLAIS), 2023)
This study aims to describe and analyze social conflict in the novel Damun Lii Fathir Shohyun: Kharotul Yahudi by Najib Kailani using the literary sociology approach of Lewis A. Coser. The analysis of social conflict is carried out based on the causes of the conflict, its form, function, and safety valve found in people's lives in the novel. This research is a qualitative research with descriptive analysis method and included in the type of library research. The data and data sources used are the novel Damun Lii Fathir Shohyun: Kharutul Yahudi karya Najib Kailani. The data collection method used the documentation method, namely by linking each discovery in the novel with the theory used. The data validity technique uses reference materials, objectivity, and persistence. Based on the analysis of social conflicts in the novel Damun Lii Fathir Shohyun: Kharutul Yahudi, two classifications of social conflicts were found. First, conflict with a positive function: 1) Killing, to set boundaries between conflicting groups, to increase group solidarity and integrity. 2) Bribery, this conflict has a positive function in the form of leading to alliances with other groups. 3) Demonstration. This conflict serves to increase the integrity of the group. Second, conflicts with negative functions: 1) bickering, the result of this conflict is a change in Dawud Harare's personality which becomes more violent towards Camelia. 2) affair, this conflict resulted in a divorce between Dawud Harare and Camelia.